Attributes of crosses and their impact on goal scoring in soccer leagues - Vantarakis, A.; Stafylidis, A. (Journal of Physical Education and Sport, 2023)
In team sports such as soccer, the percentages derived from game-related statistics can offer coaches valuable insights into a team's competitive potential and performance. This research aimed to assess the offensive strategies of soccer teams, focusing specifically on crosses originating from the sides with the intention of reaching the penalty area.